Efek topikal gel ekstrak daun kayu manis (Cinnamomum burmannii) sebagai penyembuh luka insisi pada kelinci putih jantan (Oryctolagus cuniculus) - Kasmadi, Fathnur Sani; Anggia, Sonia; Yuliawati, Yuliawati; Efendi, M. Rifqi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Cinnamon leaves (Cinnamomum burmannii) are plants that have many pharmacological effects. One of them is as a wound healer. The gel formulation becomes a convenient therapeutic solution for use. This study aimed to determine the impact of gel preparations on the healing of incision wounds in male white rabbits. The research method uses experimental methods. The test animal was injured on its back using a tool with a diameter of 2.5cm. There are five treatment groups used, namely: positive control (Bioplasenton), negative control (gel base), Formula 1 (extract 2.5%), Formula 2 (extract 5%), and Formula 3 (extract 7.5%). The results of wound healing observations were analysed using one-way ANOVA with a confidence level of 95%. The results showed that the best formula for wound healing is formula 2. Then, formula three and formula 1 had a significance value between groups of 0.05.